Changes in the frequency of food intake among children and teenagers: monitoring in a reference service - Larissa Soares Mariz; Carla Campos Muniz Medeiros; Caroline Evelin Nascimento Kluczynik Vieira; Bertha Cruz Enders; Alexsandro Silva Coura (Universidade de São Paulo, 2013)
PURPOSE: to identify changes in the food intake patterns among overweight children and teenagers, treated at a reference medical centre. METHOD: the method used is that of a cohort study, between April 2010 and April 2011. A total of 109 children and teenagers, either obese or overweight, took part in the study. The population was divided into two subgroups depending on the permanence period (more than 6 months, and less than 6 months off the treatment). The chi-square test and logistic regression were carried out. RESULTS: the group which had been longer off the treatment tended to consume more soft drinks, pasta and fried foods, and less fruit and vegetables. The group with less time showed an improvement, with a reduction of consumption of soft drinks and other goodies. There was confirmation of an increased risk for consumption of soft drinks, pasta and goodies in general, as also detachment from the treatment in adolescence. CONCLUSIONS: The group with a longer period of monitoring has had a positive change in food intake frequency. The main contribution made by this study is that of showing that multiprofissional treatment, including some nursing care, is efficient in progressively changing the food intake of children and adolescents who are overweight.